2021
DOI: 10.1016/j.isci.2021.102304
|View full text |Cite
|
Sign up to set email alerts
|

The silent pandemic: Emergent antibiotic resistances following the global response to SARS-CoV-2

Abstract: The ongoing SARS-CoV-2 pandemic has highlighted the importance of the rapid development of vaccines and antivirals. However, the potential for the emergence of antibiotic resistances due to the increased use of antibacterial cleaning products and therapeutics presents an additional, underreported threat. Most antibacterial cleaners contain simple quaternary ammonium compounds (QACs), however these compounds are steadily becoming less effective as antibacterial agents. QACs are extensively used in SARS-CoV-2 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
102
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(108 citation statements)
references
References 58 publications
1
102
0
5
Order By: Relevance
“…High empiric use of broad-spectrum antibiotics observed for COVID-19 patients is heightening concern that antibiotic overuse during the COVID-19 pandemic will exacerbate the problem of antimicrobial resistance in microorganisms of clinical significance into the future. ( 36 , 37 , 38 ) The review by Rawson et al found that 72% of COVID-19 patients had received antibacterial therapy and that recorded agents tended to be broad-spectrum antibiotics prescribed empirically in both critical and non-critical settings. ( 10 ) A meta-analysis by Langford and colleagues of 3,338 hospitalised and critical COVID-19 patients across 24 studies reported that a majority of COVID-19 patients received antibiotics (71.9%, 95% confidence interval (CI): 56.1-87.7%).…”
Section: Multi-drug Resistance and Antimicrobial Stewardshipmentioning
confidence: 99%
“…High empiric use of broad-spectrum antibiotics observed for COVID-19 patients is heightening concern that antibiotic overuse during the COVID-19 pandemic will exacerbate the problem of antimicrobial resistance in microorganisms of clinical significance into the future. ( 36 , 37 , 38 ) The review by Rawson et al found that 72% of COVID-19 patients had received antibacterial therapy and that recorded agents tended to be broad-spectrum antibiotics prescribed empirically in both critical and non-critical settings. ( 10 ) A meta-analysis by Langford and colleagues of 3,338 hospitalised and critical COVID-19 patients across 24 studies reported that a majority of COVID-19 patients received antibiotics (71.9%, 95% confidence interval (CI): 56.1-87.7%).…”
Section: Multi-drug Resistance and Antimicrobial Stewardshipmentioning
confidence: 99%
“…However, the use of antibiotics has exacerbated the emergence of antimicrobial resistance (AMR) in both commensal and pathogenic bacteria 2 . As a result, AMR, as the "silent pandemic", has become a prevalent threat to human health [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…A further challenge identified with the increased use of alcohol-based sanitisers is the apparent development of alcohol-resistance in certain multi-drug resistant bacterial strains, particularly Enterobacteriaceae [6][7][8][9][10] . It was also noted that patients were colonised earlier by multi-drug resistant organisms, including Acinetobacter and Aeromonas -a finding of significant concern in the light of the limited antibiotic choices open to a resource-constrained environment.…”
Section: Descriptive Experiencementioning
confidence: 99%
“…The unit has in the past been able to ensure low resistance rates and good antibiotic stewardship 4,11 . The theoretical mechanism of this resistance is transfer of free DNA particles between hardy bacteria resulting in alcohol resistance [7][8][9][10][11][12] . This horizontal gene transformation induces the enrichment effects of antibiotic resistance genes in resistant bacteria through the uptake of naked DNA and mobile genetic elements such as plasmids, transposons, integrons, gene cassettes, and bacteriophages.…”
Section: Descriptive Experiencementioning
confidence: 99%